ANALISIS KETEPATAN WAKTU PELAPORAN KEUANGAN PEMERINTAH PUSAT PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) MAKASSAR I - Nouvita Heban; Mariati Muhammad; Taufik Thahir (AkMen JURNAL ILMIAH, 2020)
The formulation of the problem in this study are any factors that influence the timeliness of central government financial reporting at KPPN Makassar I. This study aims to determine what factors influence the timeliness of central government financial reporting. This research was conducted at the Makassar State Treasury Service Office (KPPN) 1. The data sources used in this study were primary data and secondary data, with qualitative descriptive analysis techniques. The results of the analysis of this study explain that the factors that influence the timeliness of central government financial reporting at the Makassar Treasury Service Office (KPPN) 1 are competent human resources, information technology support, and organizational governance aspects. Financial reporting conducted by KPPN Makassar 1 is always on time according to a predetermined schedule.